2022
DOI: 10.3389/fonc.2022.858030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultrasound-Guided Deep Serratus Anterior Plane Block Combined With Dexmedetomidine as an Adjuvant to Ropivacaine Inpatient Quality of Recovery Scores Undergoing Modified Radical Mastectomy: A Randomized Controlled Trial

Abstract: BackgroundBreast cancer has overtaken lung cancer as the most commonly diagnosed malignancy and is the leading cause of cancer-related death in women. Surgery is the only possible cure for breast cancer, and the incidence of acute postoperative pain (APP) is high in breast surgery. Previous reports suggested that ultrasound-guided deep serratus anterior plane block (dSAPB) provided effective blockade to relieve pain after modified radical mastectomy for breast cancer. In fact, despite the long-acting local ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…25 The mean QoR-15 score at 24 h after surgery in the control group (132.0 AE 12.0) in this trial was higher than that reported previously in patients undergoing breast cancer surgery from China (107 to 120). 26,27 Such a discrepancy may reflect the use of multimodal analgesia (the use of dexmedetomidine and NSAIDs) in the current study. The anxiolytic properties of dexmedetomidine 28 and the anti-inflammatory effects of NSAIDs may also contribute to improved QoR.…”
Section: Discussionmentioning
confidence: 80%
“…25 The mean QoR-15 score at 24 h after surgery in the control group (132.0 AE 12.0) in this trial was higher than that reported previously in patients undergoing breast cancer surgery from China (107 to 120). 26,27 Such a discrepancy may reflect the use of multimodal analgesia (the use of dexmedetomidine and NSAIDs) in the current study. The anxiolytic properties of dexmedetomidine 28 and the anti-inflammatory effects of NSAIDs may also contribute to improved QoR.…”
Section: Discussionmentioning
confidence: 80%
“…DEX is a highly selective drug α2-adrenergic receptor agonist with characteristics including sedation, analgesia, antianxiety, inhibition of sympathetic activity, mild respiratory inhibition, and stable hemodynamics. [23][24][25] The mechanism of DEX as an adjuvant to local anesthetics enhances their effect is a multifactorial theory still being controversial, which works mainly through peripheral level, spinal cord level and supraspinal level. [25][26][27][28][29] Furthermore, there is a lack of research about the mechanism of DEX on renal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DEX reduced postoperative opioids requirements, increase patient satisfaction, and enhance postoperative recovery of gastrointestinal function. [25][26][27][28][29] In addition, DEX appears to have postoperative renal protective effects. 30 Nevertheless, so far, the exact protective mechanism of DEX in the kidney has still not been elucidated, which is thought to act mainly by inhibiting sympathetic activity, attenuating inflammation and reducing ischemic-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not clearly describe the patient' status when assessing postoperative pain, as performed in other works comparing the postoperative analgesic efficacy of different interventions in the patients undergoing breast cancer surgery. [3][4][5] The available evidence indicates that for patients undergoing breast cancer surgery, postoperative pain is more severe with movement than in a resting state. We argue that this unknown factor would have biased the results of postoperative pain assessment at the different time points.…”
mentioning
confidence: 99%
“…Fourth, this study did not observe any outcome variable of enhanced recovery after surgery protocols for breast cancer surgery, such as the time to early mobilization, the incidence of postoperative nausea and vomiting, patient's satisfaction with pain management, the time to hospital discharge, and quality of postoperative recovery. [3][4][5] In fact, these variables are very important for comparing the performance and clinical availability of different interventions for postoperative pain control. 2 Thus, we believe that this study would have provided more useful data comparing clinical values of two block modalities in patients undergoing breast cancer surgery if the design had included the assessment of the outcomes of enhanced recovery after surgery protocols.…”
mentioning
confidence: 99%